2015
DOI: 10.3746/jkfn.2015.44.10.1550
|View full text |Cite
|
Sign up to set email alerts
|

Development Process for Decreasing Bitterness of Doraji (Platycodon grandiflorum)

Abstract: This study was conducted to evaluate the improvement effects of bitter taste of doraji (Platycodon grandiflorum) with different freezing temperature conditions (-5°C, -10°C, -20°C, and -70°C). After freezing for 4 h, frozen doraji was thawed and dehydrated. Doraji frozen at -20°C showed higher contents of crude fat, crude protein, crude ash, crude fiber, and nitrogen free extract. Moisture, crude saponin, and total polyphenol contents of doraji frozen at -5°C were higher than in other samples. Weight loss of d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…The top five attributes with the highest frequency for the ideal were clean (51), sweetness (49), green apricot flavour ( 44 ) , sweet aroma ( 41 ) , and fruit aroma ( 40 ) for the 20’s age group, and sweetness (53), fruit flavour ( 44 ) , fruit aroma ( 41 ) , green apricot flavour ( 35 ) , and sweet aroma ( 34 ) for the 30‐50’s age group. This implied that these attributes could be the key drivers of liking for yakju .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The top five attributes with the highest frequency for the ideal were clean (51), sweetness (49), green apricot flavour ( 44 ) , sweet aroma ( 41 ) , and fruit aroma ( 40 ) for the 20’s age group, and sweetness (53), fruit flavour ( 44 ) , fruit aroma ( 41 ) , green apricot flavour ( 35 ) , and sweet aroma ( 34 ) for the 30‐50’s age group. This implied that these attributes could be the key drivers of liking for yakju .…”
Section: Resultsmentioning
confidence: 99%
“…A number of studies have reported bitterness in liquors to be undesirable, thereby becoming a driving factor for disliking ( 1, 2, 40 ) . The strong bitterness in products P1, P6, P7, and P8 (Table 3) could be attributed to the root‐related bitter ingredients, including ginseng (P1), balloon flower (P6, P7), and ginger (P8) possibly contributing saponin, which has a bitter taste ( 41 ) .…”
Section: Resultsmentioning
confidence: 99%
“…HPLC could be limited in distinguishing simultaneously eluted saponins based on retention time. Other reports suggested that the total contents of crude saponins were 2524 and 23,400 (mg/100 g, DW) [ 44 , 45 ]; the analysis method for crude saponins induces a large difference in contents. In addition, quantification based on the internal standard, such as the method used in this study without external standards, could generate inaccurate data in terms of determining saponin contents only.…”
Section: Resultsmentioning
confidence: 99%
“…Y1 was highest in ginseng and hawthorn odor and Y7 had the highest score for bitterness and bitter aftertaste. This result might be due to saponin, which has a bitter taste [17]. Other ingredients such as fructose, also seemed to affect sweet taste in the Y2 and Y10 samples.…”
Section: Descriptive Analysis Of Yakju Samplesmentioning
confidence: 93%